Canto em todo canto: acesso e democratização do conhecimento pela educação musical on-line - MARTINS, Karen Cristine Tavano (2025)
The research proposes an investigation on vocal music education through online education and was developed in the Graduate Program in Education (PPGE) of the University of Western Paulista (Unoeste), in Line 1: Public Policies in education, formative processes and diversity. Based on the assumptions that the Constructionist, Contextualized and Meaningful (CCM) approach indicate an alignment with contemporary trends in education that seek to respond to current challenges, such as innovative education, access and dropout. In this process, the use of digital information and communication technologies (DICT) specifically in the field of vocal music, can be a way to disentangle the domain traditionally dependent on face-to-face teaching. The guiding question of the research: Is it possible to optimize vocal music training through online education, according to the CCM approach and the use of DICT, with a view to expanding access and reducing dropout? In view of this scenario, it is questioned what the formative elements are present in a vocal music training carried out online that characterizes the experience of a constructionist, contextualized and meaningful approach. The general objective of the investigation is to analyze the possibilities for the online education of vocal music and to point out perspectives of the use of DICT as an opportunity for all, verifying the benefits in terms of time optimization, investment, distance amplifier and musical and emotional formation of the student, according to the CCS approach experienced in practice by the researcher. It is also noteworthy that the choice of a qualitative methodology developed in three stages, the first being through the narrative, which is understood by the bias of the researcher's experience during her teaching practice in vocal music. In the second stage, it was a scoping review, and in the third stage, action research, based on the bases of the CCM approach that encompasses personal narratives, literature review and participatory research, thus expanding the scope and analytical depth of the study. The action research is guided by the CCM approach, present in every choice of technique and repertoire, as well as in the formulation of the application of online classes, with singing students of different levels and ages, as well as their professions and locations. In addition, the research proposes to explore practical benefits of online music education, such as the optimization of time and investment, and the expansion of access. These aspects are fundamental for a field that faces geographical and resource limitations. As an instrument, a questionnaire applied to students was used, which aims to collect data directly from those involved, which should provide important information about the realities and challenges faced by students and educators. The questions aim to observe data in terms of advances in online education and weaknesses related to access, availability, comprehensiveness, time optimization and thus analyze the results obtained in terms of quality education and what paths can be taken for online teaching to become a perspective and future indicator in the educational environment. As a result, it is expected to contribute significantly to pedagogical practices in the music education of the future, with the benefits of online singing teaching, bringing to educator’s possibilities, methods and approaches to providing accessible training with an eye to the future of music and vocal education.